Lattice dynamics of equiatomic binary alloys - Vora, Aditya M. (Array, 2008)
Summary: In the present article, the calculations of the lattice dynamical properties of four equiatomic binary alloys viz. Na0.5Li0.5, Na0.5K0.5, Na0.5Rb0.5 and Na0.5Cs0.5 to second order in local model potential is discussed in terms of real-space sum of Born von Karman central force constants. Well known Ashcroft's empty core (EMC) model potential has been used to study the lattice dynamical properties. Instead of the average of the force constants of metallic Li, Na, K, Rb and Cs, the pseudo-alloy-atom (PAA) is adopted to compute directly the force constants of four equiatomic sodium-based binary alloys. The exchange and correlation functions due to Hartree (H) and Ichimaru-Utsumi (IU) are used to investigate influence of screening effects. Results for the lattice constants i.e. C11, C12, C44, C12-C44, C12/C44 and bulk modulus (B) obtained using the Hartree screening function have higher values in comparison with the results obtained for the same properties using Ichimaru-Utsumi (IU) screening function. The results for the shear modulus (C¢), deviation from Cauchy's relation (C12/C44), Poisson's ratio (s), Young modulus (Y), propagation velocity of elastic waves, phonon dispersion curves and degree of anisotropy (A) are encouraging for the four equiatomic Na-based binary alloys